Pemetaan Lokasi Wisata Di Kota Cirebon Dengan Penerapan Aplikasi Sistem lnformasi Geografis - Setiawan, Andi; Irma Purnamasari, Ade; Suarna, Nana (Jurnal ICT : Information Communication & Technology, 2019)
Tourism in the city of Cirebon is still tinged with a very diverse religious tour and culturation of culture that is still heavily influenced by Persia, Arabia and China. This can be seen from the palace architectural style which is still influenced by Chinese, Persian, and even Arabic cultures. The results of cultural culture with foreign nations, resulting in a variety of tourist attractions in the city of Cirebon. But the location information of the existence of tourist attractions in the city of Cirebon is still not well publicized. This research will develop an application by utilizing the geographical information system of tourist attractions in the city of Cirebon. The Geographic Information System is very appropriate to map the spread of tourist attractions in the city of Cirebon. The software development model in this study is the system life cycle or the System Development Life Cycle. The results of this study are the value of T count T table (3,230 1,665). This means that the probability is significant Î± (0.002 0.05). So that geographic information systems mapping tourist attractions in the city of Cirebon can meet expectations by users to find the shortest routes and safer locations.